PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NHT (NUMBERED HEADS TOGETHER) DENGAN MEDIA MIND MAP UNTUK MENINGKATKAN PEMAHAMAN SEJARAH DAN KREATIVITAS SISWA - Wulandari, Estri; Sariyatun, Sariyatun; Wahyuni, Sri (Candi, 2018)
The purpose of this research is to increase the history understanding and students creativity subject of class XI IPS 2 SMA N 4 Surakarta in the second semester of academic year 2016/2017 using cooperative learning type NHT (Numbered Heads Together) by using mind map media.This research is Classroom Action Research (CAR) and conducted into two cycle in which every cycle consisted of planning, acting, observing, and reflecting. The subjects of this research were 26 students of XI IPS 2 SMA N 4 Surakarta. Research sources were the teacher, students, learning process, and document. Data collecting techniques used in this research were interview, observation, test, and documentation. Data validation techniques used triangulation, source and method. This research conducted data analyzing techniques namely interactive analyzing model. The research procedure used was Lewin?s theory, namely planning, acting, observing, and reflecting.The result showed that: (1) the implementation NHT using mind map media can increase history understanding. The number of students who complected the stage pre-cycle KKM only 11 students or 42,30%. In the first cycle increased to 18 students completed the classical KKM or 69,23% after the second cycle increased again to 23 students completed the classical KKM or 88,46%. (2) The implementation of NHT (Numbered Heads Together) by using mind map media can increase students creativity. The average percentage indicator of students creativity through observation on pre-cycle is 66,92% and then increased to 75,38% in the first cycle and the second cycle increased to 82,30%. The average percentage of creativity indicators mind map group result in the first cycle is 73,33% and increased to 80% in the second cycle. The conclusion of this research is the implementation of cooperative learning type NHT (Numbered Heads Together) by using mind map media can increase history understanding and students creativity subject of class XI IPS 2 SMA N 4 Surakarta in the second semester academic year 2016/2017.